A Pilot study of Seven-Day Education Program “door-to-door” to Improve Knowledge, Attitude, and Practices towards 2019-nCoV During Stay at Home in Indonesia - Amaliyah, Eli; Aminah, . (KnE Life Sciences, 2021)
Because of the 2019-nCoV shutdown, there is a need for creative ways to spread the information to those without internet access. The aim of this study to test the feasibility of a ‘Seven-Day Education Program to Improve Knowledge, Attitude, and Practices’ in Indonesia. This research involves a quasi-experimental study with one group pre-test and post-test design, and was carried out from April to May 2020 in Serang, Banten Province, Indonesia. The education program was developed in seven days providing information door-to-door and direct consultation via a social media group for studied participants. The topics consisted of 7 themes, namely: (1) general information of 2019-nCoV; (2) transmission of 2019-nCoV; (3) signs and symptoms of 2019-nCoV; (4) what should I do if they have symptoms of COVID-19 and when should they seek medical help; (5) self-isolation; (6) how to use a mask correctly; (7) prevention of 2019-nCoV. The study had a total of 140 respondents. Knowledge of transmission routes and prevention and control for clinical presentation was enhanced after seven days experiencing the educational program. Following the intervention, the trust of the participants in winning the fight against 2019-nCoV increased. There has been a decline in the last few days before people who go to a crowded place and a rise in the proportion of people wearing masks as they go out (p<0.05). Probably this approach could be applied to reach more people in Indonesia’s rural area during this condition. A future study involving more comprehensive methods and more innovation is required in Indonesia to improve awareness, attitudes, and practices towards 2019-nCoV. Keywords: Education Program, Knowledge, Attitude, Practices, 2019-nCoV